Estimativa da necessidade de nitrogênio em cobertura no feijoeiro IAC Alvorada com clorofilômetro portátil - Mendonca Maia, Suelen Cristina [UNESP]; Soratto, Rogério Peres [UNESP]; Biazotto, Flavia de Oliveira [UNESP]; Almeida, Adriana Queiroz de (Universidade Estadual de Londrina (UEL), 2013)
The aims of this study was evaluated the efficiency of nitrogen sufficiency index (NSI) calculated with base on the measures relative chlorophyll index (RCI) leaves, measured with portable chlorophyll meter, as an indicator of time of sidedressing N fertilization and verify which value of NSI (90% and 95%) is the most appropriate to indicate the moment of N fertilization on common bean cultivar IAC Alvorada. An experiment with five N managements (M1: 200 kg ha(-1) N (40 kg at sowing + 80 kg at 15 days after emergency (DAE) + 80 kg 30 DAE); M2: 100 kg ha(-1) N (20 kg at sowing + 40 kg at 15 DAE + 40 kg at 30 DAE); M3: 20 kg ha(-1) N at sowing + 30 kg ha(-1) when chlorophyll meter readings indicated NSI < 95%; M4: 20 kg ha(-1) N at sowing + 30 kg N ha(-1) N when chlorophyll meter readings indicated NSI <90% and, M5: control (without N application)) and four replications was carried out in the rainy and dry growing seasons of the agricultural year 2009/10, in Botucatu, Sao Paulo State, Brazil. The variables RCI, aboveground dry matter, leaf N concentration, yield components, grain yield, and N use efficiency were evaluated. The NSI of 90%, calculated based on monitoring of RCI in common bean leaves with chlorophyll meter, was more effective than 95% to define need for N sidedressing in common bean cultivar IAC Alvorada, reducing the N application and improving the use efficiency of applied N.
Sidedressing nitrogen need estimation on common bean IAC Alvorada using chlorophyll meter
Keywords: Phaseolus vulgaris; chlorophyll; chlorophyll relative index; nitrogen sufficient index